Nuovi dati faunistici e tassonomici su Aleocharinae delle tribù Lomechusini, Hoplandriini, Oxypodini e Aleocharini del Sudamerica (Coleoptera, Staphylinidae). - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2009)
Taxonomic and faunal data of the 132 specimens in the Zoological Museum of the Humboldt University, Berlin, the Deutsches Entomologisches Institut, Müncheberg and the Herbert Franz Collection in the Naturhistorisches Museum, Wien, are provided. Four tribes (Lomechusini, Hoplandriini, Oxypodini and Aleocharini), 19 genera (Orphnebius, Apalonia, Myrmecoxenia, Macrogerodonia, Zyras, Abrophaena, Meoticaops, Apimela, Feluva, Idiostiba, Diacanthochara, Acrocyusa, Neocalodera, Spanioda, Tinotus, Platandria, Hoplandria, Ctenopeuca and Aleochara) and 50 species are recognized. Thirty-seven species new to science are described and illustrated. The new species are compared with similar species. Three new combinations are proposed.KeywordsColeoptera, Staphylinidae, Aleocharinae, taxonomy, South America.Nomenclatural Actsfranzi Pace, 2009 (Abrophaena), spec. n.forticornis Pace, 2009 (Acrocyusa), spec. n.catharinensis Pace, 2009 (Apalonia), spec. n.debilis Pace, 2009 (Apalonia), spec. n.laboriosa Pace, 2009 (Apalonia), spec. n.maculifrons Pace, 2009 (Apalonia), spec. n.obscura Pace, 2009 (Apalonia), spec. n.pernambucoensis Pace, 2009 (Apalonia), spec. n.seminigra Pace, 2009 (Apalonia), spec. n.tupiorum Pace, 2009 (Apalonia), spec. n.boliviana Pace, 2009 (Apimela), spec. n.brasiliensis Pace, 2009 (Diacanthochara), spec. n.colubrina (Erichson, 1839) (Feluva), comb. n. hitherto Phloeopora colubrinaminuta Pace, 2009 (Feluva), spec. n.punctulata Pace, 2009 (Feluva), spec. n.alboapicalis Pace, 2009 (Hoplandria), spec. n.diaghita Pace, 2009 (Hoplandria), spec. n.venezuelensis Pace, 2009 (Idiostiba), spec. n.boliviana Pace, 2009 (Macrogerodonia), spec. n.paraensis Pace, 2009 (Macrogerodonia), spec. n.unidens Pace, 2009 (Macrogerodonia), spec. n.boliviensis Pace, 2009 (Meoticaops), spec. n.foveaventer Pace, 2009 (Myrmecoxenia), spec. n.regia Pace, 2009 (Myrmecoxenia), spec. n.gratella Pace, 2009 (Neocalodera), spec. n.iguazuensis Pace, 2009 (Neocalodera), spec. n.amazonicus Pace, 2009 (Orphnebius), spec. n.belemensis Pace, 2009 (Orphnebius), spec. n.caligatus Pace, 2009 (Orphnebius), spec. n.maracayensis Pace, 2009 (Orphnebius), spec. n.modestus Pace, 2009 (Orphnebius), spec. n.rioensis Pace, 2009 (Orphnebius), spec. n.satan Pace, 2009 (Orphnebius), spec. n.tarapotensis Pace, 2009 (Orphnebius), spec. n.transversus Pace, 2009 (Orphnebius), spec. n.crucis Pace, 2009 (Platandria), spec. n.brasiliana Pace, 2009 (Spanioda), spec. n.carinilabiatus Pace, 2009 (Zyras (Diaulaconia)), spec. n.